Consumption of pelagic tunicates by cetaceans calves in the Mediterranean Sea - NATALIA FRAIJA-FERNÁNDEZ; ALFONSO A. RAMOS-ESPLÁ; MARÍA ÁNGELES RADUÁN; CARMEN BLANCO; JUAN ANTONIO RAGA; FRANCISCO JAVIER AZNAR (Mediterranean Marine Science, 2018)
Gelatinous zooplankton, including jellyfish, ctenophores and pelagic tunicates, constitutes fragile marine animals that live in the water column, and represent an important resource for marine food webs through their seasonal pulses. Although there is scarce evidence on the occurrence of gelatinous zooplankton in stomach contents of apex, endothermic predators such as cetaceans, the ecological significance of such observations requires consideration. In this study, we report on the occurrence of pelagic tunicates in the stomach of three individual calves of two cetacean species from the western Mediterranean, and collate all previous reports of gelatinous zooplankton in cetacean diets. We then briefly discuss the possible dietary significance of these observations.